الحوكمة... دراسة في المفهوم - بن حسين, سليمة (جامعة الوادي University of Eloued, 2015)
يعتبر مفهوم الحوكمة مفهوما مستجدّا على السّاحة العلمية, ممّا جعل أغلب المفكّرين والعلماء يختلفون حول مفهومها ولم يتفقو في إيجاد تعريف ومفهوم موحّد للحوكمة, وهو ما سنحاول فهمه في هذه الدّراسة من خلال تطرّقنا لعدّة عناصر منها: ماهية الحوكمة ونشأتها وتطوّرها, وكذا العوامل المساعدة في ظهورها (اقتصادية واجتماعية وسياسيّة), كما سنتطرّق إلى مبادئ ومؤشّرات الحوكمة من شفافيّة ومساءلة ومشاركة...الخ, بالإضافة إلى تحديد قواعدها وأهدافها ومحدّداتها الدّاخلية والخارجيّة, وكذا معاييرها... لنتعمّق أكثر في التفصيل بين مفهوم الحوكمة في الفكر الغربي والفكر العربي. Abstract: This article deals with "The Governance: study of the definition". According to the matter that the Governance has become one of the important subjects to all the institutions and the regional and international organizations during the few last decades. Especially, after the financial and economic collapses, which came as a direct result of the deficit in the governance and transparency mechanisms in some financial world institutions, and the impoverishment of its administration to the correct practice in the control and the experience and the skill. As a result of all this, the attention of the Governance definition has increased, and it became one of the essential bases which form the political and economic entities. According to the content of this article, we will divide this work to three axes: The first axe deals with different definitions of the Governance . The second one deals with definition’s problematic of the Governance between the occidental and the Arabic Thought.
Keywords: الحوكمة؛ الشفافيّة؛ المساءلة؛ المشاركة؛ الفكر الغربي؛ الفكر العربي